Inequalities in digital literacy: exploring the disparity in tangible outcomes of internet use among college students in China - Wei Fang; Chen Nie (Frontiers in Communication)
IntroductionIn the age of digitization, digital literacy plays a crucial role in ensuring that college students thrive in an increasingly digital world. While many studies have examined disparities in digital literacy focusing on access and skills, there is still a research gap concerning the tangible benefits college students derive from internet use. Using an internet outcome framework, our study scrutinizes the potential disparities in benefits derived from internet use among college students from varied social backgrounds in China.MethodsThis quantitative study employed an online survey to collect data from 463 college students across various economic regions in China, ensuring a diverse and representative sample. The survey gathered information on students' internet usage patterns and their perceived benefits across eight outcome dimensions. To identify which groups of students benefit most from internet use, we conducted logistic regression analyses examining the relationships between the eight outcome factors and socio-economic status variables. This analytical approach allowed us to assess the influence of various predictors on the likelihood of students experiencing specific internet use outcomes.ResultsWe found that students from a higher socio-economic status generally obtain more benefits from internet usage. Interestingly, female students appear to capitalize on certain advantages more than their male counterparts.DiscussionThese findings indicate that online experiences might amplify offline inequalities, suggesting that the internet could produce varied outcomes based on the student's background. Hence, we need to reevaluate the notion of digital natives and the presumed universal access to and use of digital technology among college students.